Animal Models for Anorexia Nervosa—A Systematic Review - Scharner, Sophie; Stengel, Andreas (Frontiers in Human Neuroscience, 2021)
Anorexia nervosa is an eating disorder characterized by a strong desire to lose body weight or maintain the body weight at an abnormally low level and a distorted body image which usually leads to low caloric intake and hyperactivity. The underlying mechanism and pathogenesis of anorexia nervosa is still poorly understood. In order to learn more about the underlying pathophysiology of anorexia nervosa and to find further possible treatment options, several animal models mimicking anorexia nervosa have been developed. The aim of this review is to systematically search different databases and provide an overview on existing animal models and to discuss the current knowledge gained from animal models of anorexia nervosa. For the systematic data search, the Pubmed – Medline database, Embase database and Web of Science database were searched. After removal of duplicates and the systematic process of selection, 102 original research papers were included in this systematic review. 100 studies were performed with rodents and 2 on monkeys. 18 different animal models for anorexia nervosa were used in these studies. Parameters assessed in many studies were body weight, food intake, physical activity, cessation of the estrous cycle in female animals, behavioral changes, metabolic and hormonal alterations. The most commonly used animal model (75 of the studies) is the activity-based anorexia model in which typically young rodents are exposed to time-reduced access to food (a certain number of hours a day) with unrestricted access to a running wheel. Of the genetic animal models one that is of particular interest is the anx/anx mice model. Animal models have so far contributed many findings to the understanding of mechanisms of hunger and satiety, physical activity and cognition in an underweight state and other mechanisms relevant for anorexia nervosa in humans.